THE ROLE OF MICROBIAL COMPONENT IN THE PROGRESSION OF THE ACUTE SUPPURATIVE INFLAMMATION OF TISSUES OF MAXILLOFACIAL AREA IN CHILDREN - Tkachenko, P.I.; Dobroskok, V.O.; Korotych N.М.; Kolisnyk, I.A.; Trufanova, V.P. (World of Medicine and Biology, 2018)
The paper presents the generalization of the experience acquired at the clinic of the Department of Children’s Oral Surgery and Propedeutics of Oral Surgery at Ukrainian Medical Stomatological Academy, which refers to the study of the role of microbial factor in the etiology, pathogenesis and clinical course of the acute odontogenic and nonodontogenic inflammatory processes in the maxillofacial area in 896 children with lymphadenitis, adenophlegmon and odontogenic osteomyelitis. The comparison of our own achievements and scientific studies, presented in publications, indicate about the urgent need in further routine study of the issue taking into account the possibilities of involving the state-of-the-art technical achievements and developments made in the field of microbiology.